(untitled) (Japan, 2010)
Contents: Development of the Rice Econometric Model with Endogenous Water in Lao PDR, Cambodia, Thailand and Vietnam, Development of the Rice Econometric Model with Endogenous Water in Lower Mekong Countries,...
Keywords: Food supply,Cung cấp thực phẩm